Deletion in the actual sentence in the collection of Sarsari (Journal of the College of Basic Education, 2023)
The syntax exhibitor is one of the most prominent grammatical phenomena in which the Arabic language is celebrated. The syntax exhibitor is of two parts: one of them is submission and delay, and the other is omission. Submission and delay are among the most important linguistic phenomena that give the language flexibility, as it allows the speaker to transcend the memorized ranks in his speech. Therefore, grammarians cared for him and singled out for him sections in their writings, and the introduction and the delay are of two types: with the intention of delaying, and the other: not with the intention of delaying. The origin of speech is dhikr, so omission is not permissible unless there is a presumption, which is either verbal or current.